Postpartum care knowledge and its determinants during the COVID-19 pandemic in mothers in Indonesia - Wulandari, Respati; Anggraini , Fitria Dewi Puspita; Belladiena, Alfiena Nisa; Waluyo, Dwi Eko (Science Midwifery, 2024)
Background: Maternal deaths based on obstetric status in Semarang city, Indonesia, in 2018 occurred a lot during the postpartum (15 cases). Therefore, knowledge of postpartum care is essential in improving maternal health during the postpartum. This study aims to examine the picture of postpartum care knowledge during the COVID-19 pandemic and its determinants in Indonesia. Method: Cross-sectional research design. The study involved 92 postpartum mothers in 2 Puskesmas areas in Semarang City, Indonesia. The sample size was determined using the Cochrane formula with the inclusion criteria of pregnant women with a gestational age of 32-34 weeks. The study was conducted in January 2021. The instrument uses questionnaires and purposive sampling techniques. The Chi-Square and Fisher-Exact tests in this study are used to analyze the relationship between variables. Backward stepwise logistic regression test to determine determinants of postpartum care knowledge. Result: Mothers who had poor knowledge of postpartum care were 45.7%. Poor knowledge is found mainly in the aspects of nutritious food (65.2%), vitamin A (46.7%), and personal hygiene (47.7%). Mothers exposed to digital information are more likely to have knowledge of postpartum care (OR= 2.6; CI 95%= 1,100-6,018; p=0.029). Conclusion: Knowledge of postpartum care during the COVID-19 pandemic in Indonesia is still low and needs to be improved. The use of digital media as a medium for promoting postpartum care has an opportunity to improve maternal and infant health.